Typology of tasks for the use of vocabulary in different types of speech activity - Khotamova Parvina Ilhomovna (Genius Journals, 2024)
This article focuses on the analysis of enhancing lexical skills in the process of teaching skills of communication and methods of organizing the stage of speech activity and different types of them
Keywords: Independent Statements; Quality; Communicative Interaction